2017
DOI: 10.1016/j.proeng.2017.10.778
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation for creep age forming of aluminium alloy 7050 saddle-shaped part

Abstract: Unified creep-ageing constitutive equations for aluminium alloy 7050 (AA7050) determined from experimental data were implemented into the finite element (FE) code, ABAQUS, through the user-defined subroutine, CREEP, for creep age forming (CAF) process modelling. The outer contour and yield strength of a saddle-shaped component were predicted, and the accuracy of FE prediction was analysed with experimental results. The research results show that, stress relaxation and creep deformation occur mainly in the earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…After the mold surface is compensated for springback, the forming accuracy of the component is basically not affected. [7].…”
Section: Characteristics Of Materials Autoclaves and Toolsmentioning
confidence: 99%
“…After the mold surface is compensated for springback, the forming accuracy of the component is basically not affected. [7].…”
Section: Characteristics Of Materials Autoclaves and Toolsmentioning
confidence: 99%
“…Luo et al [19] formed an Al-Li stiffened panel with complex structure features and their FE model showed that plastic and creep deformation played an equivalent role in determining springback of the stiffened panel. Stiffeners have been shown to play a key role in springback percentage and mechanical properties of formed products after CAF [20]. However detailed effect of stiffener geometry on CAF process, which is important for stiffened plate design, has rarely been reported.…”
Section: Introductionmentioning
confidence: 99%